Exploring the potential of Human Body and Brain to Synchronise with Earth Electromagnetic Resonance and Schumann Resonance A critical reflective learning journey of my Cerebral Spinal Fluid experience and the learning it evoked. Issue 1 (November 2019) - SFHEA, Dr Dinesh Bist
No abstract available